(untitled) (Vietnam Journal of Community Medicine, 2025)
for treating sacroiliac fracture-dislocations, that enables anatomical restoration, minimizes soft tissue damage, shortens hospital stay, and improve functional outcome. Objectives: Outcome of sacroiliac joints fracture-dislocation by closed reduction and percutaneous fixation by iliosacral screw. Subjects and methods: This study was carried out in Trauma and Orthopedics Department of Cho Ray Hospital from from April 2021 to August 2024, included 31 patients with age range from 16-57 years, 18 males and 13 female. Traffic accident were common cause of injury 96,8%. There were 2 patients with bilateral injuries. Among the 33 injuries classified according to the Day classification, there were 2 cases of Day II and 14 cases of Day III; according to the Denis classification, there were 10 cases of Denis II and 2 cases of Denis III; with 5 cases classified under both Day and Denis. Results: All patients were assessed functionally according to the Majeed scale: 90.4% had satisfactory results. Posoperative radiological evaluation was done according to the Lindahl scale: 69.7% had excellent results, 21.2% had good results. Two guidewires broke during surgery, and one rod loosened at fourteenth weeks post-surgery. Despite these complications, all patients achieved bone healing. Conclusion: Closed reduction and percutaneous iliosacral screw fixation technique yield good anatomical reduction and functional outcomes.